EFFECT OF GROUP-BASED HOPE INTERVENTION ON DEPRESSION IN FEMALE INMATES - Mei Rianita Elfrida Sinaga; Megah Andriany; Artika Nurrahima (Belitung Nursing Journal, 2020)
Background: Life in prison may cause negative feelings and thoughts which triggers depression for female inmates. This results in difficulty in finding purpose in life and loss of interest or motivation. Group-based hope intervention seems to be effective in decreasing depression, but it has not yet been applied in female inmates in a prison. Objective: To determine the effect of group-based hope intervention on depression level in female inmates. Methods: This study used a quasi-experimental study with pre-test post-test and control group design. Eighty-eight participants were selected using proportionate stratified random sampling, with 44 assigned into intervention and control groups. Data were collected from September to November 2019. The level of depression was measured using Beck Depression Inventory-II (BDI-II). Mann Whitney U and Wilcoxon tests were used for data analyses. Results: Both group-based hope intervention in the intervention group and routine intervention in the control group has a significant effect on depression level (p<.01). However, further analysis showed that the group-based hope intervention was much more effective than the routine group in decreasing depression level in female inmates (p<.01). Conclusion: Group-based hope intervention is effective in lowering the depression in female inmates. Therefore, this therapy can be used as a valuable intervention in nursing practice, especially in a correctional setting.